3D Spatial Distribution of Nanoparticles in Mice Brain Metastases by X-ray Phase-Contrast Tomography - Longo, Elena; Sancey, Lucie; Cedola, Alessia; Barbier, Emmanuel L.; Bravin, Alberto; Brun, Francesco; Bukreeva, Inna; Fratini, Michela; Massimi, Lorenzo; Greving, Imke; Le Duc, Geraldine; Tillement, Olivier; et al. (Frontiers in Oncology, 2021)
Characterizing nanoparticles (NPs) distribution in multiple and complex metastases is of fundamental relevance for the development of radiological protocols based on NPs administration. In the literature there have been advances in monitoring NPs in tissues. However, the lack of 3D information is still an issue. X-ray Phase-Contrast Tomography (XPCT) is a 3D label-free, non-invasive and multi-scale approach allowing imaging anatomical details with high spatial and contrast resolutions. Here an XPCT qualitative study on NPs distribution in a mouse brain model of melanoma metastases injected with gadolinium-based NPs for theranostics is presented. For the first time, XPCT images show the NPs uptake at micrometer resolution over the full brain. Our results revealed a heterogeneous distribution of the NPs inside the melanoma metastases, bridging the gap in spatial resolution between Magnetic Resonance Imaging and histology. Our findings demonstrated that XPCT is a reliable technique for NPs detection and can be considered as an emerging method for the study of NPs distribution in organs.